Ultraviolet refractometry using field-based light scattering spectroscopy - Fu, Dan (2009)
Accurate refractive index measurement in the deep ultraviolet (UV) range is important for the separate quantification of biomolecules such as proteins and DNA in biology. This task is demanding and has not been fully exploited so far. Here we report a new method of measuring refractive index using field-based light scattering spectroscopy, which is applicable to any wavelength range and suitable for both solutions and homogenous objects with well-defined shape such as microspheres. The angular scattering distribution of single microspheres immersed in homogeneous media is measured over the wavelength range 260 to 315 nm using quantitative phase microscopy. By least square fitting the observed scattering distribution with Mie scattering theory, the refractive index of either the sphere or the immersion medium can be determined provided that one is known a priori. Using this method, we have measured the refractive index dispersion of SiO(2) spheres and bovine serum albumin (BSA) solutions in the deep UV region. Specific refractive index increments of BSA are also extracted. Typical accuracy of the present refractive index technique is ≤0.003. The precision of refractive index measurements is ≤0.002 and that of specific refractive index increment determination is ≤0.01 mL/g.